Disordered eating in ethnic minority adolescents with overweight. Issue 6 (16th December 2016) - Rodgers, Rachel F.; Watts, Allison W.; Austin, S. Bryn; Haines, Jess; Neumark‐Sztainer, Dianne
Abstract: High rates of disordered eating exist among adolescents with overweight and among ethnic/racial minority adolescents. Given the lack of research examining how eating disorder risk is moderated by both overweight and ethnicity/race, this study aimed to explore interactions between ethnicity/race and overweight status on disordered eating behaviors in a population‐based adolescent sample. Cross‐sectional data from adolescents ( n  = 2, 271; 52% females) of White (23%), Black (34%), Hispanic (20%), and Asian (23%; 82% Hmong) ethnicity/race participating in the EAT 2010 study were used to examine associations between overweight status and disordered eating behaviors across ethnic/racial groups. Disordered eating behaviors occurred more frequently among adolescents with overweight compared with those without overweight across all ethnic/racial groups. Although some differences in the prevalence of disordered eating were found by ethnicity/race, particularly in girls, no consistent patterns of interaction emerged. Overweight White and Hispanic girls reported the highest risk for dieting, while the highest risk for unhealthy weight control behaviors was among overweight Black girls, and for overeating among overweight White and Asian girls. Within a society in which thinness is highly valued and being overweight is stigmatized, across diverse cultural groups, adolescents with overweight are at risk for disordered eating.